Strategies of Female-Headed Households in Managing Roles and Resources: Analysis of Family Socio-Economic Resilience in Garut Regency, West Java - Bambang Rustanto; Tuti Kartika; Aryohaji Istyawan; Rajendra Panggita Vasthu; Dwi Yuliani; Susilawati (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Female-headed households often face layered socio-economic vulnerabilities, yet their everyday strategies for sustaining family resilience remain insufficiently examined. This study explores the role and resource management strategies of female-headed households who are members of PEKKA in Garut Regency, West Java, Indonesia. Using a qualitative descriptive design, data were collected from five primary informants and seventeen supporting participants through in-depth interviews, focus group discussions, field observations, and documentation from March to August 2025. The data were analyzed using inductive thematic analysis, supported by source triangulation, member checking, reflexive discussion, and audit trail procedures. The findings show that women became household heads through diverse pathways, including widowhood, divorce, husband’s migration, illness, old age, and limited financial support. In response, PEKKA members developed interconnected strategies: diversifying livelihoods through informal work, mobilizing family labor, negotiating domestic and caregiving responsibilities, utilizing social networks, and transforming limited household assets into productive resources. The study further reveals that socio-economic resilience was not built solely through income generation, but through resource bricolage, psychosocial endurance, collective support, and women’s capacity to reorganize household roles under constraint. The main contribution of this study lies in conceptualizing the hidden power of PEKKA as everyday resilience, expressed through power within, power with, and power to. These findings suggest that empowerment programs for female-headed households should move beyond temporary assistance by strengthening livelihood access, childcare support, skills development, social protection, local facilitation, and community-based solidarity.